Pathogenic Functions of Tumor Necrosis Factor Receptor-Associated Factor 6 Signaling Following Traumatic Brain Injury - Huang, Huan; Xia, Anqi; Sun, Li; Lu, Chun; Liu, Ying; Zhu, Zhenjie; Wang, Siye; Cai, Junyan; Zhou, Xiaoyun; Liu, Su (Frontiers in Molecular Neuroscience, 2021)
Neuroinflammation contributes to delayed (secondary) neurodegeneration following traumatic brain injury (TBI). Tumor necrosis factor receptor-associated factor 6 (TRAF6) signaling may promote post-TBI neuroinflammation, thereby exacerbating secondary injury. This study investigated the pathogenic functions of TRAF6 signaling following TBI in vivo and in vitro. A rat TBI model was established by air pressure contusion while lipopolysaccharide (LPS) exposure was used to induce inflammatory-like responses in cultured astrocytes. Model rats were examined for cell-specific expression of TRAF6, NF-κB, phosphorylated (p)-NF-κB, MAPKs (ERK, JNK, and p38), p-MAPKs, chemokines (CCL2 and CXCL1), and chemokine receptors (CCR2 and CXCR2) by immunofluorescence, RT-qPCR, western blotting, and ELISA, for apoptosis by TUNEL staining, and spatial cognition by Morris water maze testing. These measurements were compared between TBI model rats receiving intracerebral injections of TRAF6-targeted RNAi vector (AAV9-TRAF6-RNAi), empty vector, MAPK/NF-κB inhibitors, or vehicle. Primary astrocytes were stimulated with LPS following TRAF6 siRNA or control transfection, and NF-κB, MAPKs, chemokine, and chemokine receptor expression levels evaluated by western blotting and ELISA. TRAF6 was expressed mainly in astrocytes and neurons of injured cortex, peaking 3 days post-TBI. Knockdown by AAV9-TRAF6-RNAi improved spatial learning and memory, decreased TUNEL-positive cell number in injured cortex, and downregulated expression levels of p-NF-κB, p-ERK, p-JNK, p-p38, CCL2, CCR2, CXCL1, and CXCR2 post-TBI. Inhibitors of NF-κB, ERK, JNK, and p38 significantly suppressed CCL2, CCR2, CXCL1, and CXCR2 expression following TBI. Furthermore, TRAF6-siRNA inhibited LPS-induced NF-κB, ERK, JNK, p38, CCL2, and CXCL1 upregulation in cultured astrocytes. Targeting TRAF6-MAPKs/NF-κB-chemokine signaling pathways may provide a novel therapeutic approach for reducing post-TBI neuroinflammation and concomitant secondary injury.